A German artist and his ties with the Romanian royal family - reflections on August Becker (1821-1887) and his role in 19th century European landscape painting - Selke, Raimond; Schaar, Torsten (Brukenthal National Museum, 2013)
This article relates to new findings concerning the life, work, and influence of the 19th century German landscape painter, August Becker (Darmstadt 1821-1887 Düsseldorf). Subsequent to the completion of a doctoral thesis concerning the oeuvre of August Becker and its publication, in 2005, some important and meaningful new discoveries have been made relating to his work. The principal focus of this article is to introduce the artist and his close ties with the royal family of Hohenzollern-Sigmaringen to international experts and to critically evaluate the new findings relating to Becker and his role as one of the most well known landscape painters for the 19th century European aristocracy.